2008
DOI: 10.1038/nature07547
|View full text |Cite
|
Sign up to set email alerts
|

Endochondral ossification is required for haematopoietic stem-cell niche formation

Abstract: Little is known about the formation of niches, local micro-environments required for stem cell maintenance. Here we develop an in vivo assay for adult hematopoietic stem cell (HSC) niche formation 1-2. With this assay, we identified a population of progenitor cells with surface markers CD45-Tie2-αV+CD105+Thy1.1- (CD105+Thy1-) that when sorted from 15.5 dpc fetal bones (fb) and transplanted under the adult mouse kidney capsule could recruit host-derived blood vessels, produce donor-derived ectopic bones through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
335
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(359 citation statements)
references
References 27 publications
19
335
4
1
Order By: Relevance
“…In fact, despite an enrichment in CD146þ cells in NAMP progeny, they could not support BM formation in vivo. Moreover, recent data [51] suggest that endochondral ossification is required for the generation of the HSC niche by a specific population of CD105þ/Thy1.1À murine osteoprogenitors directly implanted under the kidney capsule, while the CD105þ/Thy1.1þ population formed only bone through intramembranous ossification. Our data are in agreement with this report, since NAMP progeny was positive for both CD105 and the human ortholog of murine Thy1.1, CD90 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite an enrichment in CD146þ cells in NAMP progeny, they could not support BM formation in vivo. Moreover, recent data [51] suggest that endochondral ossification is required for the generation of the HSC niche by a specific population of CD105þ/Thy1.1À murine osteoprogenitors directly implanted under the kidney capsule, while the CD105þ/Thy1.1þ population formed only bone through intramembranous ossification. Our data are in agreement with this report, since NAMP progeny was positive for both CD105 and the human ortholog of murine Thy1.1, CD90 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Charles Chan has led our group in finding the mouse skeletal stem cell (SSC) that not only selfrenews but also gives rise at the single-cell level to osteocytes, chondrocytes, and up to four distinct marrow stromal cells (124). Placed under the kidney capsule in large cell numbers, SSCs form bone and cartilage in a morphologically correct manner (124)(125)(126)(127), with a bone marrow cavity containing host-derived HSCs and blood vessels. Of the stromal cell subsets, at least one was in the Whitlock clones (121), and at least three of the stroma support HSCs and hematopoiesis (124-127).…”
Section: Wwwannualreviewsorg • How One Thing Led To Anothermentioning
confidence: 99%
“…However, a similar primitive side population of HSCs isolated from the bone marrow was shown to be capable of giving rise to osteoblasts through an intermediate mesenchymal phase [71]. Studies have indicated that haematopoietic progenitor cells can be split into CD90-positive and CD90-negative fractions [72]. Both fractions appear capable of osteogenesis; however only the CD90-negative fraction has the capacity to form bone containing a central bone marrow filled cavity.…”
Section: Mesenchymal Progenitor Cellsmentioning
confidence: 99%